Dual circularly polarized series‐fed patch antenna array integrated with beam switching network. (16th May 2021) - Ahmad, Noman; Aslam, Javaria; Nawaz, Haq; Shahid, Humayun; Shoaib, Nosherwan
Abstract: A reconfigurable patch array antenna exhibiting circular polarization as well as pattern switching capabilities is presented in this work. The proposed 2 × 2 series‐fed structure is capable of generating 11 switched beams at a resonant frequency of 2.44 GHz. The work also hypothesis an unsophisticated method polarization and radiation pattern diversity. An effective reduction from 2N to N for feed ports and from N to N/2 for phase shifters has also been reported. The design is realized on a single‐layered low‐cost FR‐4 epoxy laminate having a thickness of 1.6 mm. The performance evaluation of the fabricated prototype exhibits good agreement between the computationally evaluated and the experimentally obtained results, yielding six circularly polarized and five 45° slant polarized switched beams in two‐dimensional space with appreciably high gain, acceptable side lobe level, and decent impedance matching characteristics for all constituent ports. In this work, a simple four‐port beam switching network has been proposed to synthesize the 11 switched beams at an elevation angle of 0°, ±10° and ±21° in xoz ‐plane and yoz ‐plane with both circular polarizations and 45° slant polarization. It does not require any additional digital circuit or complex geometry as reported in recent works.